2000
DOI: 10.1128/aem.66.11.4916-4920.2000
|View full text |Cite
|
Sign up to set email alerts
|

Viral Impacts on Total Abundance and Clonal Composition of the Harmful Bloom-Forming Phytoplankton Heterosigma akashiwo

Abstract: Recent observations that viruses are very abundant and biologically active components in marine ecosystems suggest that they probably influence various biogeochemical and ecological processes. In this study, the population dynamics of the harmful bloom-forming phytoplankton Heterosigma akashiwo (Raphidophyceae) and the infectious H. akashiwo viruses (HaV) were monitored in Hiroshima Bay, Japan, from May to July 1998. Concurrently, a number of H. akashiwo and HaV clones were isolated, and their virus susceptibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
139
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(150 citation statements)
references
References 32 publications
9
139
0
2
Order By: Relevance
“…At the same time, it had been shown allelopathic effects towards other algae, specifically diatoms [30]. The growth and toxicity of H. akashiwo can be mediated by hydrogen peroxide [24,31] or viruses [32,33]. In addition, and more relevant to the blooms H. akashiwo in a climate change environment, [34] showed that growth and toxicity of this alga was markedly influenced by changes in temperature and light intensity.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, it had been shown allelopathic effects towards other algae, specifically diatoms [30]. The growth and toxicity of H. akashiwo can be mediated by hydrogen peroxide [24,31] or viruses [32,33]. In addition, and more relevant to the blooms H. akashiwo in a climate change environment, [34] showed that growth and toxicity of this alga was markedly influenced by changes in temperature and light intensity.…”
Section: Introductionmentioning
confidence: 99%
“…The potential influence of viruses on phytoplankton mortality and population dynamics is well known for marine environments (for example, Bratbak et al, 1993Bratbak et al, , 1995Brussaard et al, 1996bBrussaard et al, , 2007, as verified by demonstrations of virus-induced termination of algal blooms (for example, Bratbak et al, 1993;Tarutani et al, 2000;Castberg et al, 2001;Brussaard et al, 2005b), and the potential of viruses as controlling agents for keeping algal populations at non-blooming levels (for example, Zingone et al, 1999;Larsen et al, 2001;Brussaard et al, 2005b).…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to viral infection has also been demonstrated in populations of cyanobacteria. (Waterbury and Valois, 1993;Suttle and Chan, 1994;Lennon et al, 2007), as well as in eukaryotic algae (Tarutani et al, 2000;Jacquet et al, 2002;Schroeder et al, 2003;Thyrhaug et al, 2003). For Phaeocystis, the morphology of the cells (solitary vs colonial) has been shown to influence susceptibility to viral control, with single cells being much more vulnerable to viral infection than colonial cells (Brussaard et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Their high abundance and obligately parasitic lifestyle allow viruses to exert top-down control of cellular organism populations, which is illustrated most dramatically through the implication that viruses are involved in the termination of some algal blooms (e.g., Bratbak et al, 1993;Tarutani et al, 2000;Wilson et al, 2002;Brussaard et al, 2005: Gobler et al, 2007Tomaru et al, 2007). More subtly, viruses contribute to the mortality of bacteria, phytoplankton and higher trophic levels of the aquatic food web (Proctor and Fuhrman, 1990;Suttle, 1994;Baudoux et al, 2006).…”
Section: Introductionmentioning
confidence: 99%